EFFICACY AND SAFETY OF BAN HUANG ORAL LIQUID FOR TREATING BOVINE RESPIRATORY DISEASES - Li, Bing; Zhou, Xu-Zheng; Niu, Jian-Rong; Wei, Xiao-Juan; Li, Jian-Yong; Yang, Ya-Jun; Liu, Xi-Wang; Cheng, Fu-Sheng; Zhang, Ji-Yu (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Ban Huang oral liquid was developed as a veterinary compound preparation by the Lanzhou Institute ofHusbandry and Pharmaceutical Sciences of the Chinese Academy of Agricultural Sciences (CAAS). The purpose ofthis study was to determine whether the oral liquid preparation of traditional Chinese medicine, Ban Huang, is safe andeffective for treating respiratory diseases in cattle.Materials and Methods: Acute oral toxicity experiments were conducted in Wistar rats and Kunming mice via oraladministration. The minimum inhibitory concentration of the drug against Mycoplasma bovis in vitro with the doubledilution method was 500 mg/mL, indicating good sensitivity. The results of laboratory pathogen testing, analysis ofclinical symptoms, and analysis of pathological anatomy were combined to diagnose bovine respiratory diseases in 147Simmental cattle caused by mixed infections of M. bovis, bovine respiratory syncytial virus, bovine parainfluenza virustype 3, and Mannheimia haemolytica. These cattle were randomly divided into three groups: drug treatment group 1(treated via Tilmicosin injection), drug treatment group 2 (treated with Shuang Huang Lian oral liquid combined withTilmicosin injection), and drug treatment group 3 (treated with Ban Huang oral liquid combined with Tilmicosininjection). Treatment effects were observed within 7 days.Results: The results showed no toxicity and a maximum tolerated dose greater than 20 g/kg BW. For the 87 cattle indrug-treatment group, the cure rate was 90.80%, whereas the response rate was 94.25%. The cure rate of drug treatmentgroup was increased by 14.13% in comparison with that of drug control group 1 and by 7.47% in comparison with thatof drug control group 2 (both P < 0.05).Conclusion: This study demonstrates that Ban Huang oral liquid is a safe and effective treatment for bovine respiratorydiseases, especially for mixed infection caused by M. bovis, bacteria, and viruses.